Synthesis and Analysis of the Structure, Diffusion and Cytotoxicity of Heterocyclic Platinum(IV) Complexes. Issue 47 (6th October 2015) - Macias, Freddy J.; Deo, Krishant M.; Pages, Benjamin J.; Wormell, Paul; Clegg, Jack K.; Zhang, Yingjie; Li, Feng; Zheng, Gang; Sakoff, Jennette; Gilbert, Jayne; Aldrich‐Wright, Janice R.
Abstract: We have developed six dihydroxidoplatinum(IV) compounds with cytotoxic potential. Each derived from active platinum(II) species, these complexes consist of a heterocyclic ligand (HL ) and ancillary ligand (AL ) in the form [Pt(HL )(AL )(OH)2 ] 2+, where HL is a methyl‐functionalised variant of 1, 10‐phenanthroline and AL is the S, S or R, R isomer of 1, 2‐diaminocyclohexane. NMR characterisation and X‐ray diffraction studies clearly confirmed the coordination geometry of the octahedral platinum(IV) complexes. The self‐stacking of these complexes was determined using pulsed gradient stimulated echo nuclear magnetic resonance. The self‐association behaviour of square planar platinum(II) complexes is largely dependent on concentration, whereas platinum(IV) complexes do not aggregate under the same conditions, possibly due to the presence of axial ligands. The cytotoxicity of the most active complex, exhibited in several cell lines, has been retained in the platinum(IV) form. Abstract : Platinum record : NMR characterisation and X‐ray diffraction of six dihydroxidoplatinum(IV) compounds with cytotoxic potential are presented (see figure). The self‐stacking was determined using pulse field gradient stimulated echo (PGSE) NMR spectroscopy.